EVALUASI KESESUAIAN LAHAN DAN ANALISIS POTENSI PRODUKTIVITAS TANAMAN JAHE (Zingiber officinale Rosc.) DI KABUPATEN MALANG - Iqbal Rizky Nugroho; Syahrul Kurniawan; Aditya Nugraha Putra (Jurnal Tanah dan Sumberdaya Lahan, 2020)
Suitable land is needed to support the growth of the ginger plant to increase its productivity. Climate, soil physics, soil chemistry, and land data information are needed for land suitability assessment. Land suitability evaluation technology is used to identify suitable land to grow optimally. This study aimed to map the ginger suitability in Malang district, analyze the limiting factors that most influence the growth of ginger, and analyze the relationship between land suitability class and ginger productivity in Malang district. The study was conducted using the survey method active field survey. The method for determining land suitability criteria used criteria developed by the Ministry of Agriculture of Indonesia. The data obtained were analyzed using correlation and regression. Â The results showed that the level of slope did not affect productivity. The research area, which is located in Karangploso, Singosari, Jabung, Pagak, and Kalipare Districts, has a grade of land suitability S3 (marginally suitable). Based on the results of the study, the level of slope does not affect productivity, the research areas which are located in Karangploso district, Singosari, Jabung, Pagak and Kalipare has a grade of land suitability S3 (Marginally Suitable). The characteristics of the land that most influenced the productivity of ginger according to the sequence were available-P, organic-C, CEC, and exchangeable Ca with the equation of y = 3.292 + (0.-219) X1 + 0.333X2 + 0.335X3 + 0.348X4 and RÂ²= 0,695. Land suitability class had a strong relationship with ginger plant productivity; the value of the correlation coefficient (r) was 0.766